Surgical and orthodontic treatment of impacted upper right lateral incisor (Journal of Medical Sciences, 2021)
This case report describes the successful interceptive treatment approach for young patients with complex odontoma and impacted permanent lateral incisors. The interceptive orthodontic treatment for impaction usually includes surgical excision the odontoma, surgical exposing of lateral incisor and orthodontic traction of the tooth  and space opening by summating of all nature spacing in the upper jaw with fixed appliance. If all kinds of interceptive treatments fail, the surgical intervention is an option by exposing the impacted tooth, then applying traction force to move the impacted tooth to the normal position. However, surgery is the only option in growing patients since, there is not still a chance for spontaneous eruption of the impacted tooth. In the present report, the patients presented to the orthodontic clinic with complaint of non-erupting right lateral incisor after the loss of deciduous teeth, with the eruption of lateral incisors on the contra lateral side. The treatment of this patient consisted of maxilla closing spaces to create space for permanent right lateral incisor.